An Efficient Protocol for Single-Cell Cloning Human Pluripotent Stem Cells - Singh, Amar M. (Frontiers in Cell and Developmental Biology, 2019)
Genomic manipulation of human pluripotent stem cells (hPSCs) has become essential to introduce genetic modifications and transgenes, and develop reporter lines. One of the major bottlenecks in gene editing is at the stage of single-cell cloning, which is thought to be variable across hPSC lines and is substantially reduced following a transfection. Due to the difficulty of performing fluorescent-assisted cell sorting (FACS) for single-cell isolation of hPSCs, previous approaches rely on manual colony picking, which is both time-consuming and labor-intensive. In this protocol, I provide a method for utilizing FACS to generate single-cell clones of hPSCs with efficiencies approaching 40% within 7-10 days. This can be achieved by sorting cells onto a feeder layer of MEFs in a stem cell defined medium with KSR and a Rock inhibitor, as early as 1-2 days following a transfection, streamlining the gene editing process. The approach described here provides a fundamental method for all researchers utilizing hPSCs for scientific studies.